Pengembangan Layanan Informasi Karier untuk Meningkatkan Pilihan Karier Peserta Didik Sekolah Menengah Kejuruan - Iis Solihah; Ahmad Afaq; Jean Nsengiyumva; Aji Muhammad; Salawat Fatih; Ariyanti Ariyanti; Hamidah Hamidah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
This study aims to discuss how to develop career information services to improve career choices for vocational high school students. The research was a type of research and development or Research and Development (R&D) according Borg and Gall which has been modified into five stages, namely: product analysis to be developed, initial product development, expert validation and revision, test small-scale field trials and product revisions, Large-scale field trials and final products. The research subjects were 75 students of class X-XII of Muhammadiyah Cilegon Vocational High School. The results of this study are webquest media assessment are appropriate for use as a medium to increase career choices in SMK Muhammadiyah Cilegon, the validation results of material experts 97.5% , media expert validation 83.7%, the test on 27 students scored 80.4%, the result of the large-scale media trial on 50 students obtained a score 79.3%. The results of the effectiveness test of the paired sample t-test showed that there was a different between the results of the pre-test and post-test in the form of effective webquest media products for increasing career choices (p=0.000) <0.05, meaning that there was an increase in the average student career choices in the pre-test group was 129.05 and the post-test was 150 using media webquest.